Effect of Alpinia galanga extract treatment on physicochemical properties and antimicrobial activities of cold stored fresh cut chicken breast meat / Aishah Bujang ... [et al.] - Bujang, Aishah; Idris, Norliyana Syazwani; Rizlan Ross, Ernie Eileen; Zainal Abidin, Siti Aimi Sarah (UiTM Cawangan Negeri Sembilan, 2022)
The long-term health detrimental effects of chemical additives used in food products cause worries among consumers. Hence, the use of phytochemical compounds as alternatives are being explored by many researchers. This study aimed to evaluate the effect of Alpinia galanga extract on the physicochemical properties and antimicrobial activities of chicken breast meat. The samples were immersed in galangal aqueous extract (0.5, 1.0 and 2.0%), stored at chill temperature (5±1 ºC) and monitored for 8 days. The result showed that the pH of the sample was significantly (p<0.05) increased with the increased concentration of galangal extract used. For colour values, the sample immersed with galangal had lighter colour (L*) compared to the control. During storage, redness (a*) of the control sample was reduced to a greenish hue but no changes were observed for yellowness (b*). Samples with galangal showed a gradual increase in a* and b* until day 4 followed by a gradual decline until the end of storage. No changes in the textural property observed through the penetration force of the control sample were observed. However, the penetration force of only 2% (v/w) galangal immersed sample was found to decrease after day 4. An increase in microbial growth was observed for all samples similar to control with the increase of storage time indicating no microbial inhibition effects. This study points out that the galangal extract used was able to maintain the pH, colour and textural properties of chicken meat. However, a higher concentration of more than 2% galangal extract is required to exhibit the antimicrobial properties needed to prolong the shelf-life of fresh-cut chicken meat.